Perancangan Layout Ruang Sortir dan Analisis Kebutuhan Tenaga Kerja Perusahaan Logistik - Evania Evania; Nova Sepadyati (Jurnal Titra, 2020)
The research conducted in logistics company that provides door to door delivery services. This company is expanding the consolidator building where the goods handling process is carried out. Along with the expansion of the consolidator, company wants to design a sorting room layout that can minimize the occurrence of missroute goods and increase the effectiveness of the process at the consolidator. Company also wants to evaluate the needs of its operational and administrative workforce. The design of the consolidator layout is done by taking into account the number of destinations of the sorting room, the amount of aisle needed, and the amount of sorting space based on the volume of goods. The layout design produces 3 sorting areas with a total of 115 sorting rooms. Evaluation of workforce needs is done by work sampling and calculation of full time equivalent. The determination of operational workforce needs is then followed up with a process simulation with the help of standard time calculations. The result of the calculation is to reduce 3 workers who are projected to be able to reduce labor cost by IDR 100.811.501,- annually for the company.